PERAWATAN PREVENTIF UNTUK MEMPERTAHANKAN UTILITAS PERFORMANCE PADA MESIN COOLING TOWER DI CV.ARHU TAPSELINDO BANDUNG - Endro Prihastono; Brian Prakoso (Jurnal Ilmiah Dinamika Teknik, 2017)
Maintenance management is one of the right steps to manage when a machine will be treated. Thus, the process of working machines in the factory still running smoothly so that the production process will not be hampered. Prefentive treatment steps need to be done so that the machine is always in a ready condition and can prevent the occurrence of fatal damage. In the process of oil drilling, CV. Arhu Tapselindo Bandung using cooling tower machine. The main use of the cooling tower is to remove the heat absorbed by the cooling oil circulation system used in the oil refinery. As a result, the remaining oil is cooled significantly. The maintenance strategy of the machines especially on cooling tower machine in CV. Arhu Tapselindo Bandung, among others, includes Replacement, Preventive Maintenance, Opportunity Maintenance and Machine Repair.Key Words:Utilities,Care